2014
DOI: 10.1111/apt.12999
|View full text |Cite
|
Sign up to set email alerts
|

The response of patients with bile acid diarrhoea to the farnesoid X receptor agonist obeticholic acid

Abstract: SUMMARY BackgroundBile acid diarrhoea is a common cause of chronic diarrhoea, occurring as a primary condition or secondary to ileal disease or resection. Many patients have reduced levels of the ileal hormone fibroblast growth factor 19 (FGF19), an inhibitory regulator of hepatic bile acid synthesis, secreted in response to farnesoid X receptor (FXR) activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
115
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(124 citation statements)
references
References 34 publications
5
115
0
4
Order By: Relevance
“…Our results also indicate that high lipid levels and excess body weight, along with elevated FGF19 expression, may be associated with the incidence of colon adenoma. Previous studies have suggested that FGF19 expression is stimulated by the nuclear bile acid receptor FXR (farnesoid × receptor), and that hepatic FGF19 synthesis triggers downstream signaling network [38,39]. Several genes involved in the synthesis/transport of fatty acids were reported to be repressed in FGF19 gene knock-in mice and in mice treated with recombinant FGF19 as a form of negative feedback [40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…Our results also indicate that high lipid levels and excess body weight, along with elevated FGF19 expression, may be associated with the incidence of colon adenoma. Previous studies have suggested that FGF19 expression is stimulated by the nuclear bile acid receptor FXR (farnesoid × receptor), and that hepatic FGF19 synthesis triggers downstream signaling network [38,39]. Several genes involved in the synthesis/transport of fatty acids were reported to be repressed in FGF19 gene knock-in mice and in mice treated with recombinant FGF19 as a form of negative feedback [40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…We can hypothesize that BA malabsorption that has been described to occur in MC could lead to a secondary feedback down-regulation of colonic FXR, or that alternatively inflammation in the colon leading to FXR down-regulation could render the epithelial cells more susceptible to the noxious effects of BAs. Even if preliminary, our results open the possibility of studying the use of the new FXR agonist, obeticholic acid [39,40] , in patients with refractory MC, and open avenues for a new line of research in this puzzling cause of intestinal inflammation.…”
mentioning
confidence: 86%
“…En fase experimental se están desarrollando agonistas de FXR que han mostrado cierta respuesta clínica (53,54). El ácido obeticólico ha sido evaluado en pequeños grupos de pacientes; después de 2 semanas de tratamiento en pacientes con diarrea crónica secundaria a mala-absorción de AB, se redujo la frecuencia de las deposiciones y el índice de diarrea en un 14% y 34%, respectivamente; el tratamiento con ácido obeticólico también documentó reducción de los valores sé-ricos de colesterol y triglicéridos en pacientes tratados con secuestradores de AB (55).…”
Section: Agonistas De Fxrunclassified